Exercises 12 - HigherDerivatives
Exercises 12 - HigherDerivatives
Exercises 12 - HigherDerivatives
d3 y d3 y 2x d3 y
(21) y = xe2x find (22) y = x ln(x) find (23) y = find
dx3 dx3 ex dx3
ln(x) d3 y d3 y d3 y
(25) y = x2 + 4 ex find (26) y = x2 + 1 ln(x) find
(24) y = find
3x dx3 dx3 dx3
√
ln ( x) d3 y d3 y √ d2 y
(27) y = find (28) y = ln (ex + 3) find (29) y = e x+1 find
x2 dx3 dx3 dx2
√ √
d2 y 3 x3 − 2x3 e4x √
(30) y = ln x3 + 3 find (31) y = find y 00 (32) y = x2 + 1 find y 00
dx2 2x3
√ 3x5 + x4 + x − x3 e3x
(33) y = 5x + 2 find y 000 (34) g(x) = find g 00 (x)
x2
d4 y x d2 y
(35) Find if y = cos (9 − 3x) (36) Find y 000 if y = cos (37) Find if y = ln (cos(3x))
dx4 3 dx2
(38) Find y 00 if y = ln sin3 (x) (39) Find y 00 if y = ecos(2x)−1 (40) Find y 00 if y = 3x sin(2x)
d2 y sin(x) + 3
(41) Find if y = sin (2 ln(x)) (42) Find y 00 if y = (2x − 1) cos(3x) (43) Find y 00 if y =
dx2 sin(x) + 4
d2 y d2 y x
if y = ln cos2 (2x) (46) Find y 000 if y = sin
(44) Find if y = ln (sin(5x)) (45) Find
dx2 dx2 x=0 2
*(48) Given f (x) = e2x + 23x37 − 15x21 + 7x13 − 12x4 , find f (37) (x)
1
*(49) Given f (x) = 4x21 − 3x15 + 164x7 + + e−3x , find f (47) (x)
x
1
*(50) Given f (x) = e4x−5 + 4x43 + 56x34 − , find f (45) (x)
x+2
(51) Given f (x) = 40x57 − 34x43 + x22 − e6−x + π, find f (61) (x)
−1 6 − 2x 11 − 6 ln(x)
(21) (12 + 8x)e2x x2 + 6x + 10 ex
(22) (23) (24) (25)
x2 ex 3x4
x+1 (√x
√
2x2 + 2 13 − 12 ln(x) −3e2x + 9ex e − 1) −3x4 + 18x
(26) (27) (28) (29) √ (30)
x3 x5 (ex + 3)3 4x x 2 (x3 + 3)2
45 −7 1 375
(31) x 2 − 42 e4x (32) 3 (33) 3 (34) 18x + 2 + 2x−3 − 6e3x − 9xe3x
8 (x2 + 1) 2 8 (x2 + 1) 2
1 x
(37) −9 sec2 (3x) (38) −3 csc2 (x) (39) −4 cos(2x) + 4 sin2 (2x) ecos(2x)−1
(35) 81 cos(9−3x) (36) sin
27 3
(47) (6 · 5 · 4 · 3)x2 + 54 e5x (48) 237 e2x + 23 · 37! or 237 e2x + 23(37 · 36 · 35 · · · 3 · 2 · 1)
4 · 84! 4 · (84 · 83 · 82 · · · 3 · 2 · 1)
(53) (4x + 336)ex+4 + 85
or (4x + 336)ex+4 + (54) cos(x)
x x85
(55) −254 cos(2x − 5) (56) −375 cos(3x + 1) (57) (−2)124 cos(3 − 2x) (58) (−6)45 sin(1 − 6x)
53! (53 · 52 · 51 · · · 3 · 2 · 1)
(59) −51 sin(x)−x cos(x) (60) 10! or (10·9·8 · · · 3·2·1) (61) 0 (62) or
x54 x54